2012
DOI: 10.1111/j.1440-1746.2011.06987.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis for evaluating the accuracy of endoscopy with narrow band imaging in detecting colorectal adenomas

Abstract: Endoscopy with NBI seems to improve the detection of flat adenomas, particularly with high-definition technology, but prolongs the withdrawal time. These results indicate that endoscopy routinely using the NBI system for the surveillance of adenomas may be recommended after the technique is further modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 37 publications
3
41
0
1
Order By: Relevance
“…[42][43][44][45] These analyses affirm the Cochrane review, demonstrating no significant difference between HD-NBI and HD-WLE in the detection of adenomas and polyps. One of these meta-analyses additionally compared polyp miss rates between HD-NBI and HD-WLE.…”
Section: Colon Polypssupporting
confidence: 76%
“…[42][43][44][45] These analyses affirm the Cochrane review, demonstrating no significant difference between HD-NBI and HD-WLE in the detection of adenomas and polyps. One of these meta-analyses additionally compared polyp miss rates between HD-NBI and HD-WLE.…”
Section: Colon Polypssupporting
confidence: 76%
“…Six meta-analyses assessed the ADR of the NBI system compared with that of white-light colonoscopy (WLI). [24][25][26][27][28] None of them found any difference in adenoma, small adenoma (<10 mm) or diminutive adenoma (<5 mm) detection rates. Another meta-analysis revealed a sensitivity comparing with Lucera and Exera II systems (Olympus Medical Systems).…”
Section: Narrow-band Imagingmentioning
confidence: 87%
“…Even so, a lower miss rate for adenoma in the proximal colon was achieved by performing NBI colonoscopy [10], while the detection rate of flat adenomas has increased with NBI [11]. Recent meta-analyses and systematic reviews have also shown that NBI provides no increase in adenoma or polyp detection rates compared with conventional colonoscopy [12,13]. However, after exclusion of high-definition television modalities, the rate of adenomas detection by NBI compared with white light was significantly higher, especially in patients with one adenoma.…”
Section: Characterization Of Colonic Lesionsmentioning
confidence: 99%
“…However, after exclusion of high-definition television modalities, the rate of adenomas detection by NBI compared with white light was significantly higher, especially in patients with one adenoma. The detection of flat adenoma has also increased using NBI colonoscopy [13]. Due to conflicting data from published trials, the potential benefit of NBI technique in neoplastic colonic lesions detection, especially in right-sided lesions and flat adenoma, requires further evaluation.…”
Section: Characterization Of Colonic Lesionsmentioning
confidence: 99%